PENGARUH RUTINITAS LITERASI KEAGAMAAN TERHADAP PERILAKU MAHASISWA POLITEKNIK NEGERI BANJARMASIN - Rahmah, Rahmah; Hermina, Dina; Huda, Nuril; Habibah, Nur (Yayasan Rahmat Islamiyah, 2024)
This study aims to determine the impact of religious literacy routines and emotional intelligence on the behavior of students at Politeknik Negeri Banjarmasin. This field research utilizes a quantitative approach. The sample consists of three classes of students enrolled in a Religion course at Politeknik Negeri Banjarmasin. Data collection was conducted using questionnaires. Data analysis employed simple linear regression. The results of this study indicate that religious literacy routines have a significant influence on the behavior of students at Politeknik Negeri Banjarmasin, with a table value of r = 0.419 and a calculated R value of 0.316, showing that the calculated R is greater than the table value, thus demonstrating a significant influence of routines on behavior.